Cultura organizacional no contexto da expansão da rede federal de educação profissional, científica e tecnológica: um estudo com servidores técnico- administrativos - Antunes, Cristiana Ferreira (2015)
While considering an organizational culture point of view from the society over the civil servant and upon the expanding scenario of the Brazilian Professional Educational Scientific and Technological Network (EPCT), an opportunity to study such expansion and its relationship to the organizational culture set at the Federal Institute of Paraíba (IFPB) has risen. That said, the current paper aimed at analyzing the expansion effects on the Brazilian Professional Educational Scientific and Technological Network in the organizational culture under the perspective of civil servants of IFPB. It is a qualitative and quantitative study based on a case study with a descriptive approach. Data were collected through a semi open questionnaire which was sent to all the civil servants who attend the Rectory through the institutional e-mail and which was anonymously and voluntarily answered by using the electronic form Google Drive. The answers aimed at characterizing the civil servants’ profile, identifying satisfaction levels, their perception in relation to the organization culture and the expansion process set at IFPB and to verify whether the civil servants have influenced somehow the construction of a new institution of if they have been influenced by it. The results have pointed that the civil servants are fully satisfied with their work nor with the existing culture. The vast majority sees the IFPB’s EPCT expansion as positive and fruitful, however, they indicate that it has been poorly planned and disorganized, permeated by a hierarchy and bureaucratic organizational culture that has been crystalized in the institution. Another significant group see themselves as influencing a new culture at IFPB, despite the hindrances and barriers that they face on a daily basis. To sum up, the results have pointed to the need of new managerial practices that value the organizational culture that is centered on the human being as a vector of organizational change.